BEHAVIOR INTERVENTION PROGRAM: A STUDY ON A PRIMARY LEVEL STUDENT - Erlyna Abidasari (Universitas Brawijaya, 2015)
The preliminary identification on a student (named Randy), who has Mathematical problem at primary school was derived from a classroom report, which explored everything occurred within 30 minutes interval. The data recorded becomes a baseline for ABC chart analysis to vividly portray true behavior, the potential triggers and consequent events following the occurrence of the student’s off-task behavior during Math lesson. Based on the ABC analysis, it was proven that the frequency of the off-task behavior was significant, biting nails constantly, making funny faces, walking out the classroom for motor off-task behavior; talking out of topic, making weird noises for verbal off-task behavior, and looking around, looking out the window, staring blankly to places, delaying to start doing task, as well as putting head down on table for passive off-task behavior.To construct more reliable data analysis, teacher conducted assessment interview. To ensure reliability aspect of data analysis, some other frequency data samplings were conducted in three different sessions. The rates of off-task behavior occurrence were transcribed and it came to conclusion that student’s behavior was not influencedby time difference, duration, or intervals. The off-task behavior was purely aroused by the presence of mathematics operational instructions. In order to guarantee and minimize misinterpretation, functional behavior assessment was conducted to observe personal, situational, mental, physiological, cognitive or instructional influence. Randy indicated some fluctuationsin affective, cognitive, environmental, social, physiological, as well as communicational issues. Therefore a behavior intervention plan should touch these arrays of aspects to be successful.The behavior intervention plan starts with vivid description of target behavior based on reliable data interpretation as the hypothesis. The second phase is to describe thoroughly the setting, the antecedence and the functions behavior that are problematic. By having these data, behavior replacement program is set such that can be applied step by step instructional “Narrating Number” technique to replace the off-task behaviors. Reinforcement program is also constructed to increase the likeliness to implement “Narrating Number” as well as to decrease the occurrence of off-task behavior. In order to monitor and assess the replacement program, teacher encourages self-management strategy by the help of school, environment, parents, and peers. Teacher also tries to condition environment by modifying, arranging, alternating physical entities and instructions, which are expected to boost Randy’s performance in Math. Key words: Off-task behavior, ABC chart analysis, behavior problem, behavior intervention program